Cosmopolitanisms in Muslim contexts : perspectives from the past - Maclean, Derryl N.; Ahmed, Sikeena Karmali (Exploring Muslim contexts., 2012)
Cosmopolitanism has become a key concept in social and political thought, standing in opposition to ideologies such as nationalism, parochialism and fundamentalism. Much recent discussion of this concept has been situated with contemporary Western self-perceptions, with little inclusion of information from historical Muslim contexts. This volume redresses the balance by focusing attention on instances in modern world history where cosmopolitan ideas and practices pervaded specific Muslim societies and cultures.